Identity Politics In The Public Sphere: Habermas' Discussion On Post-Secularism - Irfan Noor (Jurnal Ilmu Sosial dan Humaniora, 2026)
Religion-based identity politics remains a major issue for Indonesian nationalism. One such issue is the legitimacy of religious groups' involvement in public policy in Indonesia. In this context, Jürgen Habermas' discourse theory and its connection to his views on post-secularism are highly relevant to examine. For Habermas, the neutrality of the public sphere does not mean a space devoid of religion. In the name of democracy, religion should be placed on an equal footing with other political opinions and aspirations. Functional differentiation in modern society, which encourages the individualisation of religion, does not necessarily imply the disappearance of the influence and relevance of religion in the public sphere. However, of course, the involvement of religion in the public sphere still has limitations, namely that the particular religious language of religion must first be "translated" into a language that is acceptable to the public, namely memiliki 'epistemic status' that is acceptable to other citizens. This parallelism is referred to as a 'post-secular' society, where every citizen with religious ties has the same right to communicate with one another.